Property mapping of LDPE during 3D printing: evaluating morphological development with X-ray scattering - da Silva, Daniel P.; Pinheiro, Joao; Abdulghani, Saba; Kamma-Lorger, Christina; Martínez, Juan Carlos; Solano, Eduardo; Mateus, Artur; Pascoal-Faria, Paula; Mitchell, Geoffrey R. (Frontiers in Mechanical Engineering, 2023)
Direct digital manufacturing has been identified as one of the key tools of Industry 4.0 and it enables the creation of products directly through digital definition. Commonly known as additive manufacturing, it comprises a set of technologies that are expressively agile in small-scale productions and prototyping, in comparison to conventional mass manufacturing processes, such as injection molding of plastics. It streamlines mass customization, allows the production of highly complex objects, and has been broadly applied in several fields, from medical devices to the aerospace industry. Although a new era of design possibilities and accessibility was unveiled, most developments are focused on shape reproduction precision and the development of new feeding systems and materials. This work is focused on a shift in design for additive manufacturing, where the polymer properties, by means of the adjustment of the process conditions (extrusion rate, the write speed, and the nozzle temperature, among others), constitute a decision-making variable. In order to evaluate the morphology of semicrystalline polymers during extrusion-based 3D printing, in-situ time-resolving small and wide-angle X-ray scattering measurements were performed at the ALBA synchrotron light source in Barcelona (Spain). The goal of this research is to develop a material property mapping methodology during semicrystalline polymer melt extrusion-based 3D printing Some experiments were performed with low-density polyethylene, and we were able to confirm a correlation between the extrusion rate and writing speed of the printing with the level of preferred orientation of the chain folded lamellar crystals in the extrudate.